Anthropometric Measurements and Correlations to Glucometabolic and Cardiovascular Risk in Obese Patients Undergoing Gastric Bypass Surgery - Erica Aldenbäck; Hans-Erik Johansson (Journal of Obesity)
Abdominal obesity is associated with hypertension, increased fasting glucose, HbA1c, and cholesterol. Body mass index (BMI) is frequently used to measure and define obesity and as inclusion criteria for bariatric surgery. Sagittal abdominal diameter (SAD) has been suggested to predict the amount of visceral fat, metabolic traits, and cardiometabolic risk superior to BMI. The aim was to test whether SAD has stronger correlations to glucometabolic traits compared to BMI. One hundred and fifty-five (108 women, 47 men) morbidly obese patients undergoing bariatric surgery were evaluated before (baseline), 6 and 12 months after Roux-en-Y gastric bypass (RYGBP). BMI was reduced from 43.7 kg/m2 (baseline) to 31.3 kg/m2 (12 months) and SAD from 32.6 to 23.2 cm (both p<0.001). SAD correlated with CRP (p=0.04), fasting glucose (p=0.008), HbA1c (p=0.016), triglycerides (p=0.017), systolic blood pressure (p=0.032), and vitamin D (p=0.027). BMI correlated with CRP (p=0.006), triglycerides (p=0.016), vitamin D (p=0.002), and magnesium (p=0.037). Despite RYGBP surgery, vitamin D was significantly increased. Liver enzymes were significantly lowered after RYGBP and the change over time in SAD correlated with gamma-glutamyltransferase. SAD was superior to BMI to predict glucose disturbance and dyslipidemia implying increased use of SAD as it is cost effective and simple to perform in the clinic and could be of value when considering patients for bariatric surgery.